2011
DOI: 10.1080/00222895.2011.552078
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Distance Regulates Functional Grouping Tendencies of Agents in Team Sports

Abstract: The authors examined whether, similar to collective agent behaviors in complex, biological systems (e.g., schools of fish and colonies of ants), performers in team sports displayed functional coordination tendencies, based on local interaction rules during performance. To investigate this issue, they used videogrammetry and digitizing procedures to observe interpersonal interactions in common 4 versus 2 + 2 subphases of the team sport of rugby union, involving 16 participants aged between 16 and 17 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 14 publications
2
44
0
8
Order By: Relevance
“…Such variability was studied from a spatio-temporal point-of-view, by understanding the main factors and constraints that affect players' actions [7]. In spite of the regular dynamics of a football game [8], and considering the tactical behavior of players, the variability of players' trajectories can be seen as an interesting indicator in characterising football players within their specific tactical zones.…”
Section: Introductionmentioning
confidence: 99%
“…Such variability was studied from a spatio-temporal point-of-view, by understanding the main factors and constraints that affect players' actions [7]. In spite of the regular dynamics of a football game [8], and considering the tactical behavior of players, the variability of players' trajectories can be seen as an interesting indicator in characterising football players within their specific tactical zones.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamics results from the interpersonal interaction amongst team members [2], who cooperate to create scoring opportunities and to prevent the opponent to score [1]. Some studies have found that successful passing is a key determinant in soccer performance and the ability of teams to retain ball possession is strongly correlated to success [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of order-controlorder-control parameter interactions have identified how and why behaviours emerge in competing dyadic systems [41]. Past research has demonstrated that control parameters of interpersonal distance and relative velocity regulate a performer's actionsactions, leading to different performance outcomes [42]. For example, in rugby unionunion, results revealed specific threshold values for interpersonal distance of less than 4 m4 m, coupled with an inter-personal velocity of at least 1 m • s1 mÁs -1 , at which an attacker passes a defender [41].…”
Section: Ecological Dynamicsmentioning
confidence: 99%
“…Past studies have demonstrated that patterns of movement coordination emerge through the self-organised, spatial-temporalspatial-temporal interactions of players under specific task and environmental constraints [40][41][42]. In dynamical systems theory, self-organisation is a principle used to explain how order spontaneously emerges among different system components (e.g.…”
Section: Ecological Dynamicsmentioning
confidence: 99%